Designing motion graphics for the cultural translation of Ciak Po postpartum nutrition knowledge - Edy Chandra; Jessica Liandra (Universitas Indraprasta PGRI, 2026)
The postpartum period is a critical phase requiring adequate nutritional support for maternal recovery. However, in urban societies, traditional nutritional practices are often met with skepticism due to perceptions of irrelevance and lack of scientific credibility. Ciak Po, a traditional Chinese postpartum dietary system, exemplifies this challenge. This study aims to design and analyze motion graphics animation as a visual communication system to translate culturally rooted postpartum nutrition knowledge into a contemporary urban context. Using a qualitative design research approach, data were collected through literature review, in-depth interviews, focus group discussions, and iterative visual design development. The findings suggest that culturally adaptive motion graphics storytelling may support audience comprehension and positively influence perceptions of traditional practices. This research contributes to visual communication design by framing motion graphics as a cultural translation tool rather than merely an instructional medium.